An investigation of recombination processes in liquid junction solar cells by transient photocurrent measurements - Yalcin, Mesut; Yakuphanoğlu, Fahrettin (Elsevier Gmbh, 2020)
In this research, TiO2-RGO composites were produced using the hydrothermal method. These composite structures were used in the phonoanodes of liquid junction solar cells. This study examines recombination mechanisms in liquid junction quantum dot sensitized solar cells (QDSSCs) with reduced graphene oxide (RGO) doped TiO2 nanocomposite photoanodes, using the transient photo-current analysis method. RGO doped composite photoanode liquid junction solar cells exhibit electron lifetimes up to four times longer than pure TiO2 photoanode. This increase indicates that new electron transport paths emerged within the composite thanks to RGO, that a significant reduction was achieved in the back-transfer of electrons and that recombination mechanisms were suppressed.
Keywords: Recombination; Reduced graphene oxide (RGO); Liquid junction solar cells; Quantum dot sensitized solar cells (QDSSCs); Composite